PENERAPAN SISTEM PENERANGAN JALAN OTOMATIS DENGAN SENSOR PHOTOCELL DI DESA BABAKAN JAYA, KECAMATAN KOPO, KABUPATEN SERANG - Askarulloh, Muhammad Azam; Fahmi, Rizal; Sartini, Sartini; Haki, Ubay (Batara Wisnu : Indonesian Journal of Community Services, 2025)
Street lighting is a crucial element in improving public safety and ensuring smooth community activities during nighttime. In Babakan Jaya Village, Kopo District, Serang Regency, the existing manually operated lighting system led to unnecessary energy consumption and reduced road safety. This community service initiative introduced an automatic street lighting system equipped with a photocell sensor to enhance energy efficiency and strengthen residents’ sense of security. The implementation process involved location surveys, system design, equipment installation, testing, and official commissioning. The installed system successfully operated as intended lights automatically turned on at dusk when natural light levels decreased and switched off at dawn eliminating the need for manual control. Local residents reported noticeable improvements in both comfort and safety for nighttime activities. This program demonstrates that low-cost, simple automation technology can be effectively applied to improve rural infrastructure in an energy-efficient and sustainable manner.